Blockchain, metaverses and NFT in civil procedure and arbitration in Russia, China and USA - Elena P. Ermakova (RUDN Journal of Law, 2023)
The research is devoted to the study of new technologies - blockchain, metaverse and NFT - in civil procedure and arbitration in Russia, China and USA. The author analyzes the basic concepts and characteristics of the above technologies and gives examples of their use in judicial practice. Recent US judicial precedents (2021 and 2022), which consolidate the possibility of using blockchain and NFT technologies in court proceedings are looked at. The research aims at shaping the idea of possible application of blockchain, metaverse and NFT technologies in civil proceedings; it is based on the analysis of regulations, judicial practice of Russia, foreign countries, and scientific sources. The employed methodology is empirical methods of comparison, description, and interpretation, theoretical methods of formal and dialectical logic. Private scientific methods include legal-dogmatic method and interpretation of legal norms. The outcome of the research shows that blockchain and NFT technologies have become an effective tool used by the courts of USA and China in the analysis of electronic evidence and some other procedural actions including notification of an unknown defendant through a non-interchangeable token (NFT). The research came to the following conclusions. Blockchain transactions are often called anonymous or at least pseudonymous, but this is not the case. The issue of blockchain anonymity has been raised in several cases heard by US courts. The blockchain analysis of tools industry has allowed the court and the parties to the dispute to analyze transactions on the blockchain and in many cases trace them to an identifiable user, even if such users have taken steps to conceal their identity. It is essential to refer to the US courts experience allowing private companies to conduct Technology Assisted Review (TAR).